2013
DOI: 10.1021/bc400170r
|View full text |Cite
|
Sign up to set email alerts
|

Photocontrolled Nuclear-Targeted Drug Delivery by Single Component Photoresponsive Fluorescent Organic Nanoparticles of Acridin-9-Methanol

Abstract: We report for the first time an organic nanoparticle based nuclear-targeted photoresponsive drug delivery system (DDS) for regulated anticancer drug release. Acridin-9-methanol fluorescent organic nanoparticles used in this DDS performed three important roles: (i) ″nuclear-targeted nanocarrier″ for drug delivery, (ii) ″phototrigger″ for regulated drug release, and (iii) fluorescent chromophore for cell imaging. In vitro biological studies reveal acridin-9-methanol nanoparticles of ~60 nm size to be very effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…To this end, various specific chemical groups can also be used, which precisely exhibit affinity toward the nucleus. For instance, Jana et al 194 synthesized acridine-benzbutyrate nitrogen mustard nanoparticles, which combined the DNA with the DNA alkylation group to target at nucleus by the acridine molecule.…”
Section: Active Targeting Using Peptidesmentioning
confidence: 99%
“…To this end, various specific chemical groups can also be used, which precisely exhibit affinity toward the nucleus. For instance, Jana et al 194 synthesized acridine-benzbutyrate nitrogen mustard nanoparticles, which combined the DNA with the DNA alkylation group to target at nucleus by the acridine molecule.…”
Section: Active Targeting Using Peptidesmentioning
confidence: 99%
“…The ester bond in the conjugate can be cleaved upon visible‐light irradiation at 410 nm for 20 min, allowing the release of chlorambucil. Similarly, our group developed several photo‐controlled drug‐release systems . For example, acridin‐9‐methanol was synthesized via two steps, producing nanoparticles with a size of ≈60 nm .…”
Section: Drug/gene Delivery and Therapymentioning
confidence: 99%
“…Similarly, our group developed several photo‐controlled drug‐release systems . For example, acridin‐9‐methanol was synthesized via two steps, producing nanoparticles with a size of ≈60 nm . The presence of acridin enabled the binding of nanoparticles to DNA, ascertained by the ethidium bromide displacement assay.…”
Section: Drug/gene Delivery and Therapymentioning
confidence: 99%
“…

A new disulfide-based, imine-linked fluorescent receptor 1 was processed into organic nanoparticles (ONPs) with an average particle size of 79 nm. [6] Singh et al have reported systematic work on ONPs with the use of Biginelli-Based and other Schiff base nanoparticles that disclosed the size-dependent fluorescent properties of organic materials. Receptor 1 selectively recognized Co 2 + ions in water with a detection limit down to 88 nm.

Organic nanoparticles (ONPs) prepared from a variety of materials, including natural products, polymers and biomolecules, have found exciting applications in materials and biological sciences.

…”
mentioning
confidence: 99%
“…Moreover, ONPs dispersed in water validated the utilize of probes in drug delivery system (DDS) and cellular imaging. [6] Singh et al have reported systematic work on ONPs with the use of Biginelli-Based and other Schiff base nanoparticles that disclosed the size-dependent fluorescent properties of organic materials. [7] For biological and chemical analysis, the probe should be soluble in pure water; however most of the chemosensors are hydrophobic so freshly an innovative concept has been created, which include with the synthesis of ONPs.…”
mentioning
confidence: 99%